PENTINGNYA ETIKA PROFESI HUKUM DALAM USAHA PENEGAKAN HUKUM DI INDONESIA - Amirah Nur Hidayati J; Mazidatul Khairiyah A; Muhammad Arjati F; Achmad Shofiyullah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In upholding a good legal profession, ethics and morals are needed. The various legal professions include judges, prosecutors, advocates, notaries, and other agencies that are authorized by law. In order to work professionally and have moral integrity, the legal profession must comply with legal signs and professional ethics. Moral integrity plays an important role in problem solving. Qualifications of humanity, justice, honesty, as well as technical and ethical skills are required to be good organizers of the legal profession. Public trust can be restored with legal certainly, justice and morality.